FOUGEYROLLAS-SCHWEBEL, Dominique; LÉPINARD, Éléonore; VARIKAS, Eleni (Coordonné). Féminisme(s) Penser la pluralité. Cahiers du Genre, n. 39. - Esmeraldo, Gema Galgani Silveira Leite (Revista Estudos Feministas, 2006)
FOUGEYROLLAS-SCHWEBEL, Dominique; LÉPINARD, Éléonore; VARIKAS, Eleni (Coordonné). Féminisme(s) Penser la pluralité. Cahiers du Genre, n. 39.